Investigating Leadership Competencies and Self-Efficacy in Bahrain’s Business Process and IT Consulting Firm: A Case Study for SME Success - Jayasundera, Aloma; Allam, Zafrul (Journal of Ecohumanism, 2024)
This study emphasises the importance of leadership competencies and self-efficacy in Bahraini SME leaders as they navigate complex situations and market trends and lead their teams in meeting challenges to achieve maximum performance. The study investigates leaders' leadership competencies and self-efficacy in Bahrain's Business Process & IT Consulting organisations. By understanding these factors, the study can identify areas for development and propose initiatives to enhance the leadership skills of Bahraini SME executives, ultimately contributing to the success of their businesses. This study employed a qualitative approach to gather data from senior management within Bahrain's Business Process & IT Consulting organisation. Purposive sampling was used to select participants of various ages, social backgrounds, and experiences. The research design incorporated a combination of Action Research (AR), case studies, ethnography, and narrative analysis. This multi-method approach is a robust and well-established strategy for analysing qualitative data. An investigation into the consultancy organisation revealed a critical shortcoming in leadership competencies. The leadership team needs more competencies and self-efficacy to navigate the economic crisis challenges effectively. This deficiency, which is currently hindering their ability to develop a strong company reputation, is a crucial area that needs immediate attention. Addressing this will guide the organisation towards success in a competitive environment.